Penerapan model pembelajaran kooperatif tipe student team achievement division untuk meningkatkan hasil belajar siswa - I Wayan Suwarsa (Lembaga Pengembangan Pembelajaran Penelitian dan Pengabdian Masyarakat Universitas PGRI Mahadewa Indonesia, 2020)
This study aims to improve the learning outcomes of Prakarya dan Kewirausahaan X AP5 SMK Negeri 1 Tampaksiring students' in the 2016/2017 academic year by applying the Student Team Achievement Division (STAD) cooperative learning model. This research is classroom action research. The subjects of the study were X AP5 students’ of SMK Negeri 1 Tampaksiring in the odd semester of academic year 2016/2017, totaling 36 people. The object of research was learning outcomes Prakarya dan Kewirausahaan. Learning outcomes data were collected using learning achievement tests. Data were analyzed descriptively qualitatively. This research is considered successful if it reaches the targets set as follows: (a) a minimum grade average of 78 and 78% absorption, (b) a minimum classical completeness of 90%. Based on the results of the study, there was an increase in student learning outcomes before the study with an average of 68.19 (Categorized “less”) and absorption of 68.19% and classical completeness of 5.56%. In the first cycle, the average value was 76.39 (less category) and absorptive was 76.39% and classical completeness was 58.33%. While in the second cycle the average value of Prakarya dan Kewirausahaan was 89.44 (Categorized “good”) and absorption was 89.44% and classical completeness was 100% from 36 students. From the data analysis above, the STAD cooperative learning model has proven to be effective in improving student learning outcomes, especially in the subjects of Prakarya dan Kewirausahaan in two cycles. Penelitian ini bertujuan meningkatkan hasil belajar Prakarya dan Kewirausahaan siswa kelas X AP5 SMK Negeri 1 Tampaksiring semester ganjil tahun pelajaran 2016/2017 dengan penerapan model pembelajaran kooperatif tipe Student Team Achievement Division (STAD). Jenis penelitian ini adalah penelitian tindakan kelas. Subjek penelitian adalah siswa kelas X AP5 SMK Negeri 1 Tampaksiring semester ganjil tahun pelajaran 2016/2017 yang berjumlah 36 orang. Objek penelitian adalah hasil belajar Prakarya dan Kewirausahaan. Data hasil belajar dikumpulkan dengan tes hasil belajar. Data dianalisis secara deskriptif kualitatif. Penelitian ini dikatakan berhasil bila mencapai target yang ditetapkan sebagai berikut: (a) nilai rata-rata kelas minimal 78 dan daya serap 78%, (b) ketuntasan klasikal minimal 90%. Berdasarkan hasil penelitian, terjadi peningkatan hasil belajar Prakarya dan Kewirausahaan siswa pada data awal dengan rata-rata 68,19 (kategori kurang) dan daya serap sebesar 68,19% serta ketuntasan klasikal sebesar 5,56%. Pada siklus I nilai rata-rata sebesar 76,39 (kategori kurang) dan daya serap sebesar 76,39% serta ketuntasan klasikal sebesar 58,33%. Sedangkan pada siklus II nilai rata-rata Prakarya dan Kewirausahaan sebesar 89,44 (kategori baik) dan daya serap 89,44% serta ketuntasan klasikal sebesar 100% dari 36 siswa. Dari analisis data di atas, model pembelajaran kooperatif tipe STAD terbukti efektif dalam meningkatkan hasil belajar siswa khususnya mata pelajaran Prakarya dan Kewirausahaan dalam dua siklus.